2021
DOI: 10.2991/ahsr.k.210115.073
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Self-Care and Diabetes Distress Among Diabetic Patients

Abstract: Impact of diabetes distress on diabetes self-care practices have been widely investigated but little known about the implication of the diabetes self-care on diabetic distress. This study is a correlational study that aims to discover the prevalence of distress and its correlation with self-care behavior in type II diabetes patients. This research was conducted in January-August 2018. Findings revealed that 70.5% of respondents had low self-care behavior and 50% of respondents experienced moderate to high leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(35 reference statements)
0
0
1
Order By: Relevance
“…This study demonstrated that one of the elements influencing patients with diabetes’ distress is self-care. This result is inconsistent with previous research by Prihatiningsih and Rahmawati (2021) , demonstrating that diabetes distress does not correspond to self-care.…”
Section: Discussioncontrasting
confidence: 99%
“…This study demonstrated that one of the elements influencing patients with diabetes’ distress is self-care. This result is inconsistent with previous research by Prihatiningsih and Rahmawati (2021) , demonstrating that diabetes distress does not correspond to self-care.…”
Section: Discussioncontrasting
confidence: 99%